FMRP activity and control of Csw/SHP2 translation regulate MAPK-dependent synaptic transmission. - Leahy, S.N.; Song, C.; Vita, D.J.; Broadie, K. (PLoS Biology, 2023)
Noonan syndrome (NS) and NS with multiple lentigines (NSML) cognitive dysfunction are linked to SH2 domain-containing protein tyrosine phosphatase-2 (SHP2) gain-of-function (GoF) and loss-of-function (LoF), respectively. In Drosophila disease models, we find both SHP2 mutations from human patients and corkscrew (csw) homolog LoF/GoF elevate glutamatergic transmission. Cell-targeted RNAi and neurotransmitter release analyses reveal a presynaptic requirement. Consistently, all mutants exhibit reduced synaptic depression during high-frequency stimulation. Both LoF and GoF mutants also show impaired synaptic plasticity, including reduced facilitation, augmentation, and post-tetanic potentiation. NS/NSML diseases are characterized by elevated MAPK/ERK signaling, and drugs suppressing this signaling restore normal neurotransmission in mutants. Fragile X syndrome (FXS) is likewise characterized by elevated MAPK/ERK signaling. Fragile X Mental Retardation Protein (FMRP) binds csw mRNA and neuronal Csw protein is elevated in Drosophila fragile X mental retardation 1 (dfmr1) nulls. Moreover, phosphorylated ERK (pERK) is increased in dfmr1 and csw null presynaptic boutons. We find presynaptic pERK activation in response to stimulation is reduced in dfmr1 and csw nulls. Trans-heterozygous csw/+; dfmr1/+ recapitulate elevated presynaptic pERK activation and function, showing FMRP and Csw/SHP2 act within the same signaling pathway. Thus, a FMRP and SHP2 MAPK/ERK regulative mechanism controls basal and activity-dependent neurotransmission strength.